The Characteristics of Indonesian Digital Diplomacy - Albert Triwibowo (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
Digital diplomacy has gained momentum in recent years, especially when the COVID-19 pandemic occurred in 2020. The popularity of digital diplomacy lied in its characteristics where it offered more access to information, dialogic communication as well as transparency in diplomacy as had been implemented by many developed countries. However, recent studies have not focused yet on digital diplomacy implementation by non-developed countries. The research aimed to address the gap, by offering an analysis of the characteristics of and how Indonesia has implemented digital diplomacy. As every country had developed their respective path towards digitalisation and every Ministry of Foreign Affairs (MoFA) has its own evolution of digital diplomacy, each of which has its own characteristics in implementing digital diplomacy. The research focused on the characteristics of a country which has implemented digital diplomacy. Thus, the research tried to examine the characteristics of Indonesia’s digital diplomacy. The research argued that Indonesia’s digital diplomacy initiatives are based on a limited understanding of digital diplomacy, are sporadically pursued, and are based on an ad hoc basis. The domestic public’s interest in international issues further encourages the implementation of digital instruments. The research covered three main issues, namely the COVID-19 pandemic, the issue of palm oil, and the Rohingya crisis to establish the characteristics of Indonesian digital diplomacy. The qualitative research used primary sources in the form of interviews with Indonesian diplomats and key researchers. Furthermore, secondary sources related to Indonesia’s digital diplomacy are also used to support the research.